Modelling of fluid flow phenomena in Peirce-Smith copper converters and analysis of combined blowing concept - Chibwe, D.; Akdogan, G.; Taskinen, P.; Eksteen, Jacques (South African Institute of Mining and Metallurgy, 2015)
This investigation consists of a numerical and physical modelling exercise on flow patterns, mixing, solid-liquid mass transfer, and slag-matte phase distribution in a 0.2-scale cold model of an industrial Peirce-Smith converter (PSC). Water, kerosene, air, and sintered benzoic acid compacts were used to simulate matte, slag, injected gas, and solid additions into the PSC. The 2D and 3D numerical simulations were carried out using volume of fluid (VOF) and realizable k-ε (RKE) turbulence models to account for the multiphase and turbulence nature of the flow respectively. These models were implemented using the commercial computational fluid dynamics numerical code FLUENT. Numerical and physical simulations were able to predict, in agreement, the mixing and dispersion characteristics of the system in relation to various blowing conditions. Measurement of mass transfer indicated that fluid flow in the PSC is stratified. Blowing configurations and slag volume both had significant effects on mixing propagation, wave formation, and splashing. As a potential process alternative to increase conversion efficiency, we propose a combined blowing configuration using top lance and lateral nozzles. The numerical simulations were conducted on combined as well as lateral blowing conditions, and the results of the combined concept are encouraging.